Lekra Vs Manikebu: Perlawanan Majalah Sastra terhadap Politik Kebudayaan Pemerintah Masa Demokrasi Terpimpin (1961-1964) - Nurmalia Susanti; Nana Supriatna; Yeni Kurniawati Sumantri (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This research emerged from the author’s interest in cultural magazines’ involvement regarding a political situation in Indonesia. The main problem discussed “how was the Sastra magazine’s resistance against cultural politics of the Leaded Democracy periodin 1961-1964?” The main problem elaborated into four research questions, namely: (1) how was the background of Sastra magazine’s publication?; (2) how was the culture concept from Sastra magazine’s perspective?; (3) how was the Sastra magazine’s efforts to defended its perspective in addressing anti-mainstream cultural concepts?;and (4) how was the impact received by the Sastra magazine due to maintaining the anti-mainstream cultural concept?. The method used in this study is the historical method which is divided into four stages, such as heuristics, criticism, interpretation, and historiography. Based on the study, it can be explained that Sastra published in 1961 was a continuation of Kisah, the publication of this magazine has acted as aneffort to provide good reading for the community. In its development, Sastra has its own view of the cultural concept of the Leaded Democracy era, that Indonesian culture is an honest culture that was born from the conscience of the people based on humanity, not based on the slogans of party interests. That was considered not following the spirit of revolution that had not been completed at the time, which led to attacks from various parties, especially from the Lekra. Sastra maintained its stance, one of which was through its involvement in the Manifes Kebudayaan, which was a statement of a group of artists regarding Indonesia’s national culture. But not even a year, theManifes Kebudayaan declared forbidden by President Sukarno because he considered competing with the Indonesian Political Manifesto. The prohibition statement became a trigger for Sastra to disappear from circulation because it was labelled as a tool for the reactionaries.